PEMBIASAA OLAHRAGA SENAM SEHAT BERSAMA GUNA MENINGKATKAN KESADARAN PENTINGNYA BEROLAHRAGA UNTUK KESEHATAN PADA ANAK DI SDN KARANG TUMARITIS - Muhamad Rizky Firadus Rahmat; Desty Endrawati Subroto; Qosmal Muzzaki; Panji Gumelar; Wildan Maulana; Nazwa Zahralova (Jurnal Padamu Negeri, 2025)
This research aims to explore the effectiveness of a joint healthy exercise habit program in increasing children's awareness of the importance of exercise for health. With the increasing prevalence of health problems related to a sedentary lifestyle among children, fun and educational interventions have become increasingly important. The program involves a series of exercise sessions designed to encourage active participation in children, accompanied by education about the benefits of exercise for physical and mental health. This study aims to evaluate the influence of the habit of healthy exercise together on children's awareness at SDN Tumaritis regarding the importance of exercise for health. The method used in this research is a direct approach in the field, where exercise sessions are held every Saturday for eight weeks. During the activities, observations were made to assess the children's level of participation and changes in their behavior regarding physical activity. The results of the study showed a significant increase in children's awareness about the benefits of sport after participating in the gymnastics program. In addition, there was a clear improvement in children's physical fitness as measured through physical fitness tests. These findings indicate that healthy exercise habits can be an effective strategy in increasing children's awareness and interest in physical activity.